ETHNOBOTANY STUDY OF SEAWEED DIVERSITY AND ITS UTILIZATION IN WARAMBADI, PANGUHALODO AREAS OF EAST SUMBA DISTRICT - Anggadiredja, Jana Tjahjana (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2009)
This paper reports the ethnobotany study of seaweed diversity in Warambadi –Panguhalodo areas of East Sumba District, the island of Sumba. The study recorded19 genera of 54 species of seaweed, which were utilized as food or edible seaweed.The group consisted of 17 species of green algae, 17 species of red algae, and 20species of brown algae. The study also reported that 18 genera of 38 species weretraditionally utilized for medicinal purposes as herbal medicine. The herbal speciesconsisted of 7 species of green algae, 13 species of red algae, and 18 species ofbrown algae.Seaweed is traditionally consumed as food in various forms: raw as salad and vegetable,as pickle with sauce of allspice or with vinegar, as relish or sweetened jellies and alsocooked for vegetable soup. As herbal medicine seaweed is usually used for traditionalcosmetics, as antipyretic and antiseptic, as vermifuges, and treatments for cough andasthma, hemorrhoid, nosebleed and boils, goiter and scrofula, stomach ailments andurinary diseases.Indigenous knowledge on seaweed still exist and are continually employed bypeople living in particular areas such as the Sumba and Sabu ethnic groups. Yet,the knowledge is gradually decreasing due to localities, socio-economic change andcultural development.